Effect of Honey, Dates Extract Mixed with Water, and Sport Drink Energy Gel X on Blood Glucose And Lactic Acid Levels - Al-Fanjari, Ahmad Syauqi; Bahri, Samsul; Syafriani, Rini; Kurniati, Neng Fisheri (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
The availability of glucose is very influential on the performance of athletes. In addition, the level of fatigue can also inhibit performance in the body. One Prevention to minimize the level of fatigue and improve performance by consume beverages rich in carbohydrates. The purpose of this study was to determine the effect of honey mixed with water, date extract mixed with water, and energy gel x on glucose and lactic acid levels. Method: This study used a double-blind crossover design with four periods. This research was conducted in futsal field of Ramuna, Jati Asih, Bekasi. The subjects were 20 students of futsal teams of SMA Future Gate Bekasi with healthy status. Each period of study subjects checked blood glucose and lactic acid levels before playing futsal with moderate intensity (70% -80% HR) for 4 periods. Each period is separated by a washout for 7 days. Glucose and lactic acid levels were measured immediately at 0, 20, 40, and 45 minutes to determine the significant difference in the effect of treatment on glucose and lactic acid levels. Results: The three carbohydrate beverage administration treatments had no significantly different carbohydrate content. Two or more data averages are said to have significant differences if the value (P<0.05). That’s group II, III, and IV. There was a significant difference in blood glucose and lactic acid levels between the 20th and 40th minutes and the difference between the 20th and 45th minutes. This can be seen from both values in Group II (P=0.001) where (P<0.05). Conclusion: of the three, honey (Apis mellifera Linnaeus) mixed with water, dates (Phoenix dactylifera) extract mixed with water, and sports drink energy gel X have a significant effect on increasing blood glucose levels and decreasing lactic acid levels in the men's futsal team of Future Gate Bekasi High School.